2021
DOI: 10.3390/ijerph18178995
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Screening by Anti-SARS-CoV-2 Antibody Seropositivity: Clinical and Epidemiological Characteristics, Comorbidities, and Food Intake Quality

Abstract: Developing countries have reported lower molecular diagnostic testing levels due to a lack of resources. Therefore, antibody tests represent an alternative to detect exposure to SARS-CoV-2 and analyze possible risk factors. We aimed to describe and compare the clinical-epidemiological characteristics and the quality of food intake in Mexican individuals with a positive or negative test to antibodies against SARS-CoV-2. We carried out antibody tests and applied a survey to 1799 individuals; 42% were positive, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…We observed that only half of the subjects in the non-comorbid group produced antibodies, whereas all subjects in comorbid groups were IgG-positive to the anti-SARS-CoV-2 nucleocapsid. Similarly, Macedo et al detected high seropositivity in all comorbid groups analyzed, where DM and HTN were the comorbidities with the highest incidence [ 21 ].…”
Section: Discussionmentioning
confidence: 94%
“…We observed that only half of the subjects in the non-comorbid group produced antibodies, whereas all subjects in comorbid groups were IgG-positive to the anti-SARS-CoV-2 nucleocapsid. Similarly, Macedo et al detected high seropositivity in all comorbid groups analyzed, where DM and HTN were the comorbidities with the highest incidence [ 21 ].…”
Section: Discussionmentioning
confidence: 94%
“…Identification of SARS-CoV-2 variants was also performed using the Master Mut Kit assay (Genes2Life G2LMUSC-14, Guanajuato, Mexico) as previously described [ 21 ]. The LaDEER eligibility criteria for RT-PCR testing of suspected COVID-19 patients has previously been published in greater detail [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The association between binding antibodies and diabetes is less clear. Six studies reported positive associations, including greater antibody levels [ 47 , 66 ] and percentage of seropositivity [ 62 , [69] , [70] , [71] ], among people with metabolic abnormalities (DM and related indicators [glucose, HbA1c]), relative to those without. Five studies showed no differences in seropositivity by DM status [ 49 , [72] , [73] , [74] , [75] ], whereas one study found an inverse association between seropositivity and DM [ 76 ].…”
Section: Prevaccination Eramentioning
confidence: 99%
“…Eight studies showed that SARS-CoV-2 binding antibody seropositivity [ 69 , 73 ], specifically anti-N [ 67 , [74] , [75] , [76] ] and anti-S receptor binding domain (RBD) [ 49 ], and anti-S titers [ 66 ] did not differ by hypertension or elevated blood pressure. Two studies reported positive associations between SARS-CoV-2 Ig levels and hypertension [ 47 , 80 ]; 2 studies found inverse associations between neutralizing antibody titers or binding antibody seropositivity and hypertension [ 48 , 76 ].…”
Section: Prevaccination Eramentioning
confidence: 99%